2019
DOI: 10.5957/josr.10180093
|View full text |Cite
|
Sign up to set email alerts
|

Spray Formation and Structural Deformation During the Oblique Impact of a Flexible Plate on a Quiescent Water Surface

Abstract: In naval hydrodynamics most the reseach on the impact of the hull of a vesel to the water surface has focused primarily on mapping the forces on the hull and much less to the formation of the spray. The latter is the topic of the present work, where the spray generated by the impact of a flat plate on a quiescent water surface is studied by experiments and simulations at different impact Froude numbers. Overall two types of sprays are formed: Type I, which is a cloud of droplets and ligaments generated at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The slamming experiments were carried out in a towing tank system, as shown in figure 6(a). Details of the towing tank system have been discussed in [1]. An aluminum plate (1219 mm × 381 mm × 7.9 mm) was mounted on a carriage with a pitch angle α = 5 • and a roll angle β = 10 • .…”
Section: Experiments Arrangementmentioning
confidence: 99%
See 1 more Smart Citation
“…The slamming experiments were carried out in a towing tank system, as shown in figure 6(a). Details of the towing tank system have been discussed in [1]. An aluminum plate (1219 mm × 381 mm × 7.9 mm) was mounted on a carriage with a pitch angle α = 5 • and a roll angle β = 10 • .…”
Section: Experiments Arrangementmentioning
confidence: 99%
“…There have been efforts for investigating the slamming phenomenon, and many of them have focused on the study of fundamental problems such as the impact of a flat or wedge plate on the water surface (e.g. [1,2]). In such studies, monitoring the structural responses is important for better understanding of the complex fluid-structure interaction during the slamming event.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. (2019) performed an experimental study on the oblique impact of a flexible and a rigid plate with non-zero pitch and roll angles. Under the same motion trajectory, it is found that the maximum deformation of the flexible plate occurs at a more downstream location for a greater impact speed.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of gravity on the impact at low initial impact velocity is pointed out by the authors. Experimental investigations on the vertical impact of an inclined nearly rigid plate with prescribed impact velocity on a water surface were performed by Wang et al (2016) and . In the effect of gravity on the evolution of the spray over time was characterized by an instantaneous Froude number associated with the temporally varying nominal submerged length of the plate.…”
Section: Introductionmentioning
confidence: 99%